2018
DOI: 10.1007/s00414-018-1906-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of whole body diffusion-weighted post-mortem magnetic resonance imaging in timing of perinatal deaths

Abstract: ObjectivesDiffusion-weighted MRI provides information regarding body water movement following death, which may be an imaging marker of post-mortem interval (time since death; PMI) or maceration (degree of tissue degradation during intra-uterine retention) in perinatal deaths. Our aim was to evaluate the relationship between maceration, PMI and body organ apparent diffusion coefficient (ADC) values in a cohort of subjects across a wide gestational range.MaterialsWhole body post-mortem MRI with diffusion-weighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…The same study, however, found no similar relationship between perinatal deaths and stillbirths for unknown reasons [ 20 ]. Diffusion-weighted magnetic resonance imaging (DWI) with better models can also be useful in determining apparent brain diffusion coefficient (ADC) and degree of maceration during the gestation and post-mortem interval [ 21 , 22 ]. While PMMRI continues to be on the frontlines for increasing diagnostic capabilities, creating a cost-effective way to construct this apparatus so patients can have more accessible diagnostic tools in medical facilities throughout the nation could be pivotal.…”
Section: Reviewmentioning
confidence: 99%
“…The same study, however, found no similar relationship between perinatal deaths and stillbirths for unknown reasons [ 20 ]. Diffusion-weighted magnetic resonance imaging (DWI) with better models can also be useful in determining apparent brain diffusion coefficient (ADC) and degree of maceration during the gestation and post-mortem interval [ 21 , 22 ]. While PMMRI continues to be on the frontlines for increasing diagnostic capabilities, creating a cost-effective way to construct this apparatus so patients can have more accessible diagnostic tools in medical facilities throughout the nation could be pivotal.…”
Section: Reviewmentioning
confidence: 99%
“…As part of the internal validity of this study, we obtained excellent concordance between the FLV/weight estimated by MRI and the liver weight at post-mortem assessment. Liver weight is directly affected by the maceration status of the fetus ( 32 , 33 ), being more affected in type-III maceration. However, 82% of the TOP-fetuses in our series had type-I maceration.…”
Section: Discussionmentioning
confidence: 99%
“…В основе повышения значений коэффициента диффузии в легких лежат, по мнению авторов [38], посмертные изменения в виде экстравазации жидкой части крови в окружающие ткани. Следует также отметить, что в результате многофакторного регрессионного анализа значений измеряемого коэффициента диффузии в ткани миокарда, селезенки, коркового слоя почек, печени и поясничной мышцы при посмертной диффузионно-взвешенной МРТ установлено наличие значимых его взаимосвязей с выраженностью процессов мацерации [39]. Однако для оценки выраженности мацерации авторами использовалась оригинальная ее градация: отсутствие (0 баллов), умеренная (1) и выраженная (2), позволяющая судить только о степени ее выраженности, но не конкретном времени наступления гибели плода.…”
Section: посмертная мрт оценка давности внутриутробной гибели плодаunclassified